Network meta-analysis of randomized control trials evaluating the effectiveness of various probiotic formulations in patients with type 2 diabetes mellitus - Abdallah R. Allam; Mohamed Basyouni Helal; Mohamed Salah Alhateem; Mohamed Ashraf Shehab; Ahmed Gamal Elshaar; Mohamed Ahmed Saeda; Fatma Magdi Ibrahim; Ahmed Maher Khalil; Abdelrahman Mohamed Mahmoud (Diabetology & Metabolic Syndrome)
Abstract Background Type 2 diabetes mellitus (T2DM) is a global health concern with a rising prevalence. Recent studies indicate that the gut microbiota plays a role in the development of T2DM, making probiotics a promising avenue for proper glycemic control. This network meta-analysis aims to comprehensively assess various probiotic therapies in the management of T2DM. Methods All published randomized controlled trials (RCTs) were identified through searches in PubMed, Cochrane, and Web of Science. Included RCTs were evaluated using the Cochrane risk of bias tool 2. The retrieved data were pooled, where the mean difference (MD) and a 95% confidence interval (CI) were calculated using the R program version 4.2.1. Results A total of 62 RCTs were included, with baseline hemoglobin A1c (HbA1c) ranging from 5.71% to 9.5%. Among all interventions, the combination of Bifidobacterium bifidum W23, Bifidobacterium lactis W52, Lactobacillus acidophilus W37, Lactobacillus brevis W63, Lactobacillus casei W56, Lactobacillus salivarius W24, Lactococcus lactis W19, and Lactococcus lactis W58 achieved the greatest reduction in fasting plasma glucose (FPG) [MD = − 73.50; 95% CI: − 113.13 to − 33.86]. The greatest reduction in HbA1c was observed with yogurt containing Lactobacillus acidophilus La5, Bifidobacterium Bb12, and Cucurbita ficifolia [MD = − 1.59; 95% CI: − 3.07 to − 0.12]. For total cholesterol, the top-performing intervention was yeast containing Saccharomyces cerevisiae [MD = − 43.67; 95% CI: − 57.07 to − 30.27]. Conclusion Our network meta-analysis suggests that specific probiotic formulations, including combinations of various strains of Lactobacillus, Bifidobacterium, yogurt-based formulations containing Lactobacillus acidophilus La5, Bifidobacterium Bb12 with Cucurbita ficifolia, and Saccharomyces cerevisiae yeast, may be beneficial as adjunctive therapies for improving glycemic control and lipid profiles in patients with T2DM. However, these findings should be interpreted with caution due to variability in study designs, probiotic regimens, and potential risk of bias.